2015
DOI: 10.11604/pamj.2015.20.159.4677
|View full text |Cite
|
Sign up to set email alerts
|

Impact du traitement antirétroviral sur le profil biologique des enfants VIH positifs suivis au Centre Hospitalier et Universitaire de Yaoundé au Cameroun

Abstract: IntroductionL'objectif de ce travail était d’évaluer l'impact du traitement antirétroviral sur le profil biologique des enfants VIH positifs suivis au Centre Hospitalier et Universitaire de Yaoundé au Cameroun.MéthodesIl s'agissait d'une étude rétrospective réalisée de Mai 2003 à Décembre 2012 au CHU de Yaoundé au Cameroun. Pour cette étude, nous avons obtenu une clairance éthique.RésultatsL’âge moyen était de 54.02±46.34 mois. The sexe ratio était de 0.96 en faveur des garçons. Le diagnostic s’était fait tard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
1
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
3
1
0
2
Order By: Relevance
“…The results of the current study showed that 52.8% of patients were males. This observation of higher proportion of males over females was previously reported in similar studies 9,10 . Patients within the age group of 31–45 years old represented the highest proportion among the study population; which is also consistent with findings reported from other countries in the region 11‐15 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of the current study showed that 52.8% of patients were males. This observation of higher proportion of males over females was previously reported in similar studies 9,10 . Patients within the age group of 31–45 years old represented the highest proportion among the study population; which is also consistent with findings reported from other countries in the region 11‐15 .…”
Section: Discussionsupporting
confidence: 92%
“…This observation of higher proportion of males over females was previously reported in similar studies. 9,10 Patients within the age group of 31-45 years old represented the highest proportion among the study population; which is also consistent with findings reported from other countries in the region. [11][12][13][14][15] It is also worth noting that in this study, the majority (52.8%) of the patients were married.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Les résultats obtenus par Bréma [ 4 ] au Mali, signifiant un gain considérable de Lymphocytes T CD4 au cours du traitement ARV. L'étude de Ginette CMK et al a constaté une augmentation du taux moyen de toutes les variables étudiées avec une différence significative [ 13 ]. Van Dijk et collaborateurs, ont observé également dans leur série une augmentation du taux moyen des CD4 à M6 de 13% par rapport au taux moyen à l'initiation (respectivement 16,3% à M0 et 29,3% à M6) [ 14 ].…”
Section: Discussionunclassified
“…L'un des objectifs du traitement est de restaurer l'immunité. Le suivi biologique met en évidence une augmentation significative du taux de lymphocytes CD4/mm 3 dès le 6e mois après l'instauration du traitement antirétroviral [ 10 , 13 ]. La charge virale a très peu été réalisée dans notre étude 6 réalisations pour 5 patients.…”
Section: Discussionunclassified